How people with intellectual and developmental disabilities on collaborative research teams use technology: A rapid scoping review. Issue 1 (16th July 2021) - Hwang, I‐Ting; Hallock, Taye M.; Schwartz, Ariel E.; Roth, Stephanie; Pfeiffer, Beth; Kramer, Jessica M.
Abstract: Background: We conducted a rapid scoping review to identify how inclusive research teams use technology during the research process that could support remote collaboration during public health emergencies like the COVID‐19 pandemic. Method: We searched three databases and conducted a hand search. Two independent reviewers screened 1498 abstracts and titles for inclusion criteria; 81 full text articles were further reviewed; 47 were included. We extracted information about each type of technology, categorised technology used during the research process, and documented described accommodations. Results: We identified 47 articles and 94 examples of technologies used by people with intellectual and developmental disabilities throughout the research process: team formation and team function (38), data collection (19), data analysis (17) and dissemination (20). Conclusions: Technology use by team members with intellectual and developmental disabilities demonstrates promise for remote research collaborations during public health and climate emergencies and teams with members living in diverse locations.